(untitled) (GRESIA, 2025)
This qualitative and quantitative study was made to establish the environmental impacts of cigarette during the extraction stages of tobacco, transportation, cigarette production, product marketing and its end of life. From the information obtained we suggest multiple production alternatives for reducing the negative impact that occur during the life cycle of the cigarette. The analysis was developed following the parameters given by the ISO 14040 Standard. The stages of pre-sowing and planting showed significant environmental impacts generated from the application of pesticides. The negative effects of the disposal of cigarette butts and packs are also highlighted. When implementing improving alternatives, the extraction stages of tobacco, cigarette production, product marketing and end of life, the environmental impacts decreased about 60% in most of the stages.